Agroforestry : farming with trees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Agroforestry is a term which has only recently come into general use. It is used - and practised - most widely in tropical countries because of its advantages in optimizing production while reducing soil erosion. While the name may be new, the...